Comportamento estratégico no Supremo Tribunal Federal - Mateus Morais Araújo (2017)
This dissertation consists of an analysis of the judicial behavior theories, especially the attitudinal and strategic models. I conduct that analysis through the judgments of the Brazilian Supremo Tribunal Federal (STF). To do that, it presents a literature review of the judicial behavior and the political role of the STF, in addition to a series of tests confirming the hypothesis that the STF decisions are mainly strategic. Finally, it presents a case study on the trial of Penal Action 470, also known as “mensalão”, witch concatenates the ideas developed in previous chapters to elaborate an interpretation that explains the results of the judgment through strategic behavior.